Preliminary Evaluation of Recombinant EPC1 and TPx for Serological Diagnosis of Animal Cystic Echinococcosis - Liang, Yuqing; Song, Hongyu; Wu, Maodi; Xie, Yue; Gu, Xiaobin; He, Ran; Lai, Weiming; Jing, Bo; Peng, Xuerong; Yang, Guangyou (Frontiers in Cellular and Infection Microbiology, 2020)
Animal cystic echinococcosis (CE) is one of the most important helminthic diseases and affects many mammalian intermediate hosts. Practical and effective diagnosis is crucial for animal CE control. Two different recombinant antigens derived from Echinococcus granulosus, Echinococcus protoscolex calcium binding protein 1（rEg-EPC1）and thioredoxin peroxidase (rEg-TPx), were evaluated in this study to detect the specific immunoglobulin G (IgG) in sheep and goat with CE by the indirect enzyme-linked immunosorbent assays. The diagnostic effect of the above-listed proteins was determined to their sensitivity and specificity and compared with hydatid cyst fluid, two previously reported immunogenic recombinant proteins (dihydrofolate reductase and P29), and two commercial kits available in China. Of these, the best diagnostic results were obtained in the anti-TPx IgG ELISA, with 92.6% sensitivity, 98.8% specificity, and no cross-reactivity with anti-Eg95 IgG. Recombinant E. granulosus thioredoxin peroxidase shows good potential for serological diagnosis of animal cystic echinococcosis.